Nursing home staff perceptions of challenges and coping strategies during COVID-19 pandemic in China - Zhao, Si (Geriatr Nurs, 2021)
BACKGROUND: First-line nursing staff are responsible for protecting residents, the most vulnerable population, from COVID-19 infections. They are at a high risk of being infected with COVID-19 and experience high levels of psychological distress. AIMS: To explore the challenges and coping strategies perceived by nursing staff during the COVID-19 pandemic in China. METHODS: In April,2020, we conducted a qualitative study using in-depth semi-structured interviews with nursing staff. Participants were selected from seven nursing homes in three cities in Hunan Province, China. RESULTS: A total of 21 nursing staff participated in the study, including seven nurse managers, seven registered nurses and seven nursing assistants. Three main themes were identified. Different groups encountered different sources of stress and adopted various coping strategies to fulfil their responsibilities. CONCLUSIONS: Nursing home staff were underprepared for dealing with COVID-19-related challenges. Educational programs to improve the ability to deal with COVID-19 prevention and control are needed.